Development Of Props Media “Smiling Clock” For Teaching Speaking Skill - Khamidah, Niswatul; Rofi’ah, Siti; Widiarini, Widiarini (Lembaga Penelitian dan Pendidikan Mandala, 2023)
In the seventh grade of MTs Ma'arif Kawedusan, it was found that the understanding of English material was relatively low, because there weren't enough learning tools available to spark kids' interest in studying English.The purpose of the research is to develop props media Smiling Clock for teaching the speaking of telling time material.. In this learning media development research used the ADDIE method, where in this method researchers carried out as many as five stages. Analysis, design, development, implementation, and evaluation. After going through several processes until the product was finished, the researcher validated it. The first validation, the instrument validation, was based on instrument experts' evaluations, it received a score of 93% with the category